2016
DOI: 10.18632/oncotarget.8740
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 promoted migration and invasion binding with TCF12 by promoting EMT progress in gallbladder cancer

Abstract: The identification of prognostic markers for gallbladder cancer is needed for clinical practice. Histone deacetylases (HDACs) play an important role in tumor development and progression by modifying histone and non-histone proteins. However, the expression of HDAC1 in patients with gallbladder cancer is still unknown. Here, we reported that HDAC1 expression was elevated in cancerous tissue and correlated with lymph node metastasis and poorer overall survival in patients with GBC. Knockdown of HDAC1 using lenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Identification of the key mechanism underlying GC is imperative. In previous studies, TCF12 has been shown to play a key role in the diversity of human cancers . We thus investigate whether TCF12 was differentially expressed in GC tissues.…”
Section: Discussionmentioning
confidence: 96%
“…Identification of the key mechanism underlying GC is imperative. In previous studies, TCF12 has been shown to play a key role in the diversity of human cancers . We thus investigate whether TCF12 was differentially expressed in GC tissues.…”
Section: Discussionmentioning
confidence: 96%
“…A global H3K27 deacetylation was also observed, suggesting it is a key epigenetic event in ZEB1-induced transcriptional reprogramming [86]. In addition to EMT-TFs, HDAC1 is co-purified with TCF12 while the elevated expression of TCF12 and HDAC1 correlates with poor prognosis of gallbladder cancer patients [87], indicating that this HLH transcription factor could also targets HDACs for epithelial gene silencing during EMT. Intriguingly, HDAC6 and SIRT1 have been shown to counteract p300-catalyzed acetylation on Cortactin and thus enhance its F-actin binding ability to facilitate EMT and tumor progression [88,89].…”
Section: Permissive Histone Modifications In Emtmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT), several oncogenic cues have been suggested could increase GBC cells growth and stemness through promoting EMT process [14, 15]. Hypoxia-inducible factor-1α subunit (HIF-1α), a key factor in resisting oxidative stress, could also promote aggressive phenotype of cancer cells through different types of intracellular signal transduction pathways, including EMT activation [16-22].…”
Section: Introductionmentioning
confidence: 99%